1981
DOI: 10.1177/0310057x8100900205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience with Epidural Morphine

Abstract: Epidural analgesia with morphine sulphate was administered to 130 patients. Of 96 patients with postoperative pain, 74 experienced good analgesia, 14 obtained a fair degree of pain relief, and in eight the method was unsatisfactory. Of the 34 non-operated patients 30 had good pain relief and the method failed in one. The most common cause of failure of analgesia was an incorrectly placed epidural catheter. Urinary difficulties and pruritus were encountered as the principal side-effects. One patient suffered de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The incidence of urinary retention in this study is comparable to that of others using extradural morphine [11,12]. Of those patients who reported nausea or vomiting, 0.9% (seven patients) had undergone orthopaedic procedures, and it was felt that prophylactic antiemetic treatment was unnecessary.…”
Section: Discussionsupporting
confidence: 66%
“…The incidence of urinary retention in this study is comparable to that of others using extradural morphine [11,12]. Of those patients who reported nausea or vomiting, 0.9% (seven patients) had undergone orthopaedic procedures, and it was felt that prophylactic antiemetic treatment was unnecessary.…”
Section: Discussionsupporting
confidence: 66%
“…Rudra (1985), [12] Harcus A.H. (1980), [24] T.A. torda (1981), [25] have shown Buprenorphine were remarkably free from any significant cardiovascular insults attributable to this drug from our study, we also confirm the same, we ahave considered bradycardia when pulse rate was less then 60/min. and hypotension when reduction in blood pressure was more 20% of basal level and we had found hypotension in 4 cases and bradycardia in 4 cases -intraoperatively and postoperatively no patient had bradycardia or hypotension in study group.…”
Section: Pain Scoringsupporting
confidence: 82%
“…T.A. Torda (1981), [18] administered morphine epidurally for postoperartive analgesia and achieved good analgesia in most of patients with duration ranged from 6 hours up. Lanz et al (1984), [19] observed that with 0.15 mg. Buprenorphine, men duration of analgesia was 6 hrs., while with 0.3. mg, it was about 12 hrs.…”
Section: Pain Scoringmentioning
confidence: 99%
“…In the reported clinical series the incidence varies widely. Torda and Pybus [186] noted that only one of 24 patients required catheterization, but in other series frequencies of 22% [158] and 39% [108] have been reported. Urinary retention occurred in 79% of patients undergoing ano-rectal surgery [86].…”
Section: Urinary Retentionmentioning
confidence: 92%